Licking of pine sap by Greenfinches "Carduelis chloris" and Goldfinches "Carduelis carduelis" - Kwieciński, Zbigniew; Pawlak, Paulina; Przybylska, Katarzyna (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In 2011 and 2012, an unusual and so far not described foraging behaviour of two finch species was observed in the Barycz valley, W-Poland. Several times Greenfinches "Carduelis chloris" broke off fresh shoots of Scots pine ("Pinus silvestris") and then licked up the leaking sap. Afterwards, Goldfinches "Carduelis carduelis" also licked up the sap from the same spot. We hypothesize that both species take advantage of the antiseptic nature of "Pinaceae" sap.
Keywords: wróblowe; ornitologia